C. elegans dopaminergic D2-like receptors delimit recurrent cholinergic-mediated motor programs during a goal-oriented behavior. - Paola Correa; Brigitte LeBoeuf; L René García (PLoS Genetics)
Caenorhabditis elegans male copulation requires coordinated temporal-spatial execution of different motor outputs. During mating, a cloacal circuit consisting of cholinergic sensory-motor neurons and sex muscles maintains the male's position and executes copulatory spicule thrusts at his mate's vulva. However, distinct signaling mechanisms that delimit these behaviors to their proper context are unclear. We found that dopamine (DA) signaling directs copulatory spicule insertion attempts to the hermaphrodite vulva by dampening spurious stimulus-independent sex muscle contractions. From pharmacology and genetic analyses, DA antagonizes stimulatory ACh signaling via the D2-like receptors, DOP-2 and DOP-3, and Gα(o/i) proteins, GOA-1 and GPA-7. Calcium imaging and optogenetics suggest that heightened DA-expressing ray neuron activities coincide with the cholinergic cloacal ganglia function during spicule insertion attempts. D2-like receptor signaling also attenuates the excitability of additional mating circuits to reduce the duration of mating attempts with unproductive and/or inappropriate partners. This suggests that, during wild-type mating, simultaneous DA-ACh signaling modulates the activity threshold of repetitive motor programs, thus confining the behavior to the proper situational context.